PALATABILITAS DAN STRATEGI PENGELOLAAN PAKAN Rusa timor (Rusa timorenis) di PENANGKARAN WISMA DAERAH KABUPATEN SUMBAWA - Sofia Mutmainnah; Andi Chairil Ichsan; Maiser Syaputra (Jurnal Sylva Scienteae, 2021)
To determine feed palatability, feed recommendation and feed managementstrategies Rusa timor (Rusa timorensis) by using two individuals male and female deer that can represent selected by method focal animal sampling. Show that the level of feed consumption Rusa timor (Rusa timorensis) male as much 4,79/kg/day and as many females 4,59/kg/day. Palatability of males is as much as the Kalamenta (L. hexandra)type 14,01 %, the female deer are as many kinds of tendrils 14,40 %. The highest nutrient content of the feed is owned by Suluran (M. peltata), Rumput teki (C. rotundus), Gamal (G. sepium) and Kalamenta (L. hexandra) type feed. Recommended feed given is the main feed with the type of Suluran (Merremia peltata) , kalamenta (L. hexandra) dan Gamal (Gliricidia sepium). Recommended feed given is the main feed with the type of Gamal (G. sepium) and alternative feed with the type of Kalamenta (L. hexandra). The feed management strategy used is the S-T strategy, which is always doing regular feeding and minimizing expenditure on the purchase of feed by utilizing feeds around the breeding area and conducting a system of planting feed plants in captivity so that deer can utilize feed contained inthe breeding area and increase safety for animals.Keywords: Palatability, Recommendations , Strategies, Rusa timor